Giant Gastrointestinal Stromal Tumor Presenting as a Palpable Abdominal Mass: An Unusual Presentation - Patil, Sachin (International Scholarly Research Network, 2011)
Gastrointestinal stromal tumors (GIST-) account for the majority of mesenchymal tumors arising within the gastrointestinal tract. GIST presenting as a palpable abdominal mass is extremely rare. We report four additional cases of a GIST presenting as an abdominal mass along with a pertinent review of the literature. Twenty five cases of GISTs presenting with an abdominal mass, including 4 cases discussed here, have been reported in the world literature since 2001. The mean duration of symptoms was 152.7 days. Twenty one of 25 (84%) patients received surgical resection. The mean tumor size was 17.2 cm, with an average mitotic index of 7.6 per 50 high power fields. Thirteen of 14 (92.9%) patients had a high-risk tumor. Five patients were disease-free at a mean followup of 11 months, 2 patients had stable disease and 2 patients had progressive disease, and one patient had a partial response. In conclusion, symptomatic patents have an increased incidence of high-risk tumors and metastases at presentation. Adjuvant therapy with imatinib improves disease-free survival in patients with large abdominal GIST tumors, but no change in overall survival was noted. Finally, GISTs should be considered in the differential diagnosis of an abdominal mass in an elderly patient.